Algorithmic Landscapes: Algorithms and walking as ways of dwelling and constructing the landscape - Montanari, Matheus da Rocha (2021)
This paper presents a discussion on landscape and its algorithmic dimension through the Algorithmic Landscapes art project. More than a backdrop where the action happens, the landscape, itself, is discussed as something in the order of action, contemplating spatio-temporal dimensions that encapsulate a series of physical, cultural, technological and aesthetic elements. We understand that with an increasing algorithmic logic permeating the world, we have to take into account these elements as agents and constituents of the landscape. In the first part of the text, we address these conceptual aspects. The second part of the text describes the development of the Algorithmic Landscapes experimental project. The project is a set of iterative actions in cities of Brazil and France. These actions include an algorithmic performance, the development and analysis of images by Artificial Intelligence software, and a series of poetic operations on these images that are finally displayed as a video mapping piece on the façade of a building.